2018
DOI: 10.1016/j.archoralbio.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of oropharynx and lower respiratory tract in critical patients: Risk of ventilator-associated pneumonia

Abstract: Bacterial species may migrate rapidly from mouth and upper airways during orotracheal intubation which contributes to the pathogenesis of VAP. There were associations between VAP and Enterococcus faecalis, Fusobacterium periodonticum, Gemella morbillorum, Neisseria mucosa, Propionibacterium acnes, Prevotella melaninogenica, Streptococcus oralis, Streptococcus sanguinis, Treponema denticola, Treponema socransckii, and Veillonella parvula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
0
30
1
Order By: Relevance
“…Various types of oral microorganisms can be detected from the lungs due to different risk factors. Periodontal pathogens such as Treponema denticola, P. gingivalis, Fusobacterium nucleatum, Actinobacillus actinomycetemcomitans and Veillonella parvula , have been detected in the lungs of ICU patients ( Kumar, 2017 ; de Carvalho Baptista et al, 2018 ). The tongue dorsum is one habitat niche of oral microbes, there the dominant microflora are Prevotella and Veillonella , which are associated with an increased risk of death due to pneumonia in older, frail patients ( Asakawa et al, 2018 ; Kageyama et al, 2018 ).…”
Section: Co-infection Of Oral Microbiome and Sars-cov-2 In The Lungsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of oral microorganisms can be detected from the lungs due to different risk factors. Periodontal pathogens such as Treponema denticola, P. gingivalis, Fusobacterium nucleatum, Actinobacillus actinomycetemcomitans and Veillonella parvula , have been detected in the lungs of ICU patients ( Kumar, 2017 ; de Carvalho Baptista et al, 2018 ). The tongue dorsum is one habitat niche of oral microbes, there the dominant microflora are Prevotella and Veillonella , which are associated with an increased risk of death due to pneumonia in older, frail patients ( Asakawa et al, 2018 ; Kageyama et al, 2018 ).…”
Section: Co-infection Of Oral Microbiome and Sars-cov-2 In The Lungsmentioning
confidence: 99%
“…Ventilator-associated pneumonia (VAP) frequently occurs in patients requiring mechanical ventilation, leading to high mortality, with an incidence from 5% to 67% depending on the population studied and the diagnostic criteria used ( Barbier et al, 2013 ; Torres et al, 2017 ). In the process of orotracheal intubation, bacteria can rapidly migrate from the oral cavity and upper respiratory tract into the lungs ( de Carvalho Baptista et al, 2018 ). Another risk factor is that ICU mechanical ventilation patients find it difficult to clear oral secretions via swallowing or coughing ( Paju and Scannapieco, 2007 ).…”
Section: Co-infection Of Oral Microbiome and Sars-cov-2 In The Lungsmentioning
confidence: 99%
“…In this study, we found that OTUs positively associated with worsening clinical parameters, which reflected hepatic decompensation. Several OTUs were enriched in the late stage of LC and were all of oral origin, including E. corrodens, G. haemolysans, Leptotrichia, F. periodonticum, Selenomonas sp., A. odontolyticus, and S. moorei, which have been reported to cause opportunistic infections, such as a liver abscess or endocarditis, or have been associated with colorectal cancer (Malik et al, 2010;Woo et al, 2010;Chao et al, 2011;Warren et al, 2013;Revest et al, 2016;Eriksson and Lif, 2017;Yu et al, 2017;de Carvalho Baptista et al, 2018). Intestinal colonization of bacteria of oral origin has been associated with many diseases.…”
Section: The Role Of Indicator Otus In the Progression Of Hbv Infectionmentioning
confidence: 99%
“…Evidence suggests a correlation between oral care and pulmonary infections. 21 Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, and Enterobacter are potentially harmful bacteria that may colonize in the mouth. Gram-negative bacteria can multiply three-fold in 3-6 hours on the tooth surface.…”
Section: Preoperative Preparationmentioning
confidence: 99%